Superficial sediments and their relation to polyehaete families in a subtropieal embayment, Mexico - Méndez, Nuria (Universidad de Costa Rica, 1998)
The soft bottoms in front of Mazatlan Bay and "Isla de la Piedra" Peninsula were studied to produce maps (depth, grain size and organic matter content in sediments). Sixty samples were óbtained with a 30 x 30 van Veen grab (4-21 m depth) and polychaetes were extracted from 21 subsamples. Grain size ranged from -1.05 phi (gravel) to 3 .81 phi (very fine sand), with fme sand predominl\ting. Organic matter content in sediment was 0.91-3.06 % (most values = 1-2 %). Thirty polychaete families (905 individuals/m2 in mean) were found, and Cirratulidae, Spionidae, Onuphidae, and Pilargiidae were domiuant. Pearson's correlation of grain size.